Pupal Distribution of Dacus dorsalis Hendel in Relation to Host Plants and its Pupation Depth - Ibrahim, Yusof; Mohamad, Rosli (1978)
Studies on pupal distribution of Dacus dorsalis Hendel in rdation to host plants and its depth of pupation were conducted. Samples from papaya trees gave significantly (P<O.05) higher pupal count compared to those from guava, starfruit, and jackfruit. No significant differences were obtained among samples from the latie)' three host plants. The pupae were also found to be almost evenly distributed under the trees. The results obtained also showed that this insect prefers to pupate at 2 cm and 3 em soil depth.